New Social Problems in Medicine (Open Herald: Periodical of Methodical Research, 2024)
Content analysis of publications in sociology of medicine had showed some actual social  problems of medicine, which became interested for Russian researches in last 10-15 years. These  difficulties  don’t limited  all social  problems  of medicine  and  therefore  it seems appropriate to new researches in the given direction